Digital currency in China: pilot implementations, legal challenges and prospects - Chaowei Xu; Banggui Jin (Juridical Tribune, 2022)
Digital currency is supported by blockchain as the underlying technology, and possesses the characteristics of decentralization, programmability, and security verification based on cryptographic principles. In fact, it can be divided into legal digital currency and non-legal digital currency depending to whether the digital currency is issued by the competent authority. China’s legal digital currency (DC/EP) has implemented early and already has a certain scale of development. This article examines the legal issues that arise from the implementation of a legal digital currency in China, issues that Chinese lawmakers inevitably face. These legal issues may arise at both domestic and international levels, such as personal privacy protection, currency sovereignty conflicts, potential cross-border crimes risks. This article emphasizes that on the one hand, the development of legal digital currency must be carried out within a reasonable legal framework to avoid new systemic risks caused by the development of technology. On the other hand, it is also necessary for China to put in place as soon as possible an appropriate legal framework, explore the international cooperation of diversified supervision as well to ensure the healthy development of legal digital currency.